Facing the development challenge in Mozambique: an economywide perspective - Tarp, Finn; Arndt, Channing; Jensen, Henning Tarp; Robinson, Sherman; Heltberg, Rasmus (International Food Policy Research Institute, 2002)
Following Mozambique’s economic collapse in 1986, the country began a wide-ranging process of reform, with the support of the international community. The diagnosis was of an economy that failed to maintain monetary control, consumed beyond its means, focused production excessively on nontraded goods, and relied on inefficient and inflexible microeconomic structures. Nevertheless, Mozambique was also at war. The pace of stabilization and structural adjustment quickened after 1992, when, concurrent with the demise of apartheid, civil strife finally came to an end. After more than 10 years of adjustment, the reform program has now been essentially implemented. Yet, this does not imply, as shown in this study, that sufficient conditions for sustained economic development are in place. Mozambique remains very poor, and even under highly optimistic assumptions about the future, the development process is set to last for decades. This report attempts to respond to some of the basic development challenges facing Mozambique and to provide both qualitative and quantitative insights for policymaking in the years to come. Throughout, the issues addressed are approached from an economywide perspective ....Finally, this study aims to demonstrate that sophisticated analytical tools can be of significant value, even in “data-poor” situations. The need for a clear perspective and in-depth understanding of the socioeconomic complexities of the country in question stands out. However, while the analyses in this report are Mozambique specific, the basic analytical approach is replicable and could be brought to bear on other countries both within and outside Africa." -- From Authors' Introduction.